Less is More: In Search of Sustainable Investment Premium - Ding, Jianglin Dennis (International Journal of Economics and Financial Issues, 2024)
Considering the inconsistency among various ESG ratings from major agencies, and the conflicting research findings: from superior returns and reduced risk to indicating no significant difference or even underperformance, this study uses a single indicator instead of a complicated scoring system to examines “green” firms categorized with zero fossil fuel exposure, comparing their performance to “brown” firms with fossil fuel exposure investments. The findings indicate that market value-weighted portfolios of these "green" stocks outperform their counterparts, demonstrating potential financial benefits of sustainable investing based on a single indicator. The study employs the Fama-French three-factor model and cross-sectional analysis, showing that "green" portfolios yield higher abnormal returns and exhibit different risk profiles compared to "brown" (non-fossil-fuel-free) portfolios. The research underscores the need simply and standardize ESG metrics to enhance comparability and reliability, thereby aiding investors in making informed decisions aligned with sustainability goals.